Visual feast : contemporary food staging and photography - Klanten, Robert, 1964-; Kouznetsova, Anja, ....- (Berlin : Gestalten, 2017)
Visual Feast reveals a world where food is both an art medium and an edible eccentricity.We eat with our eyes. People love to stage and take photos of their food. Driven by Instagram and the advertising industry, stylists, gourmands, and photographers continually invent new ways of presenting food as both delectable and radical. Visual Feast presents work nonpareil from this growing scene. Sharing photos of food has become entrenched in our daily lives. Visual Feast celebrates the interplay between a myriad of styles: maps created from vegetables, lobsters painted gold to adorn tables, jelly molded into witty dishes. These images can be readily found on social media, in magazine Edited byials, or transformed into infographics. Food photographers and stylists create innovative images that make mouths water, eyes widen, and nostrils inhale imagined scents. Quenching creative curiosities and satisfying even the keenest of artistic palettes, Visual Feast explores food staging and exists as a tome of inspiration for those immersed and intrigued by its yummy and alluring realm.
Keywords: Photography